Modal dispersion characteristics and waveguide dispersion of an optical waveguide having a new unconventional core cross-section - Singh V.; Joshi M.; Prasad B.; Ojha S.P. (My University, 2025)
In this article, we present a simple and practical analytical approach based on scalar wave approximation to estimate the modal dispersion characteristics and cutoff condition of an optical waveguide having an arbitrary and uniform core cross-section. This structure represents the core of a circular waveguide which is compressed at both the ends of a diameter. We choose the new and appropriate orthogonal coordinates for the proposed waveguide structure and impose the boundary conditions under the weak guidance approximation to get the modal eigen value equation. Using this equation, we achieve numerical results in the form of dispersion curves and cutoff frequencies. Further, representing the normalised frequency parameter as V and normalised propagation constant as bʹ, the dependence of (Formula Presented) on V has been obtained and shown graphically. A brief comparison of the proposed waveguide and the circular waveguide has also been made in respect of the number of sustained modes and waveguide dispersion. © Journal of Electromagnetic Waves and Applications. All rights reserved.